Tier II intervention in the intermediate grades: the effects of reciprocal teaching (RT) on standardized literacy assessments - Roop, Theodora D. (Kansas State University, 2018)
The purpose for this study is to look at the effects of a specific comprehension strategy—Reciprocal Teaching (RT; Palincsar & Brown, 1983,1984) on the performance of intermediate elementary students in the intermediate elementary grades on a standardized literacy assessment. The study was carried out in two implementation stages: a pilot with a small sample of fourth graders and a full-scale study with third, fourth, and fifth graders in a suburban public school district in the Midwest. The pilot study was implemented in two fourth grade classrooms, a total of 39 students, nine of which met the criterial for the experimental group who scored below the 25th percentile on an AIMSweb Maze 2016 fall benchmark. The full-scale study consisted of 269 students in grades three, four, and five across the same district, except for the fourth graders who previously were involved in the pilot. There were 71 students who met the criteria for the experimental group of scores below the 25th percentile on an AIMSweb Maze 2016 winter benchmark; however, after signed consent forms were returned, 59 participated. The students in the experimental group participated in intervention utilizing RT for approximately four weeks in Tier II small groups, instructed by classroom teachers at each elementary school. Regression discontinuity was used to determine the effect of RT on the students’ comprehension as indicated by their spring benchmark scores. The results of the pilot study showed a significant main effect in the scores along the regression line, indicating a positive effect for the intervention. Regression discontinuity analysis between groups indicated that a significant main effect exists for the intervention group. The full-scale study examined the effects per grade level for all students and with a set caliper for students whose scores were four points above and below the cut-off point, or winter 2016 benchmark, for the grade level. The results of the full-scale study focusing on all scores showed a significant main effect in the scores along the regression line, indicating a positive effect for the intervention for all grades; the effect was significant for all grades, but mostly for fourth and fifth graders. Regression discontinuity analysis between groups indicated that a significant main effect exists for the intervention group. When looking at scores within the caliper of four points above or below the benchmark, all scores showed a significant main effect in the scores along the regression line, indicating a positive effect for the intervention for all grades. Regression discontinuity analysis between groups indicated that a significant main effect exists for the intervention group within the caliper at each grade level.
Keywords: Intervention; Reading comprehension; MetacognitionReciprocal teaching